Immuno-combined treatment versus radio-combined treatment in limited-stage small-cell lung cancer - Li Tong; Xiaomi Li; Mingming Hu; Minghang Zhang; Yishuo Wang; Kai Zhang; Qunhui Wang; Tongmei Zhang; Baolan Li (Therapeutic Advances in Medical Oncology)
Background: Although the approval of immunotherapy in patients with extensive-stage small-cell lung cancer (ES-SCLC) has significantly improved the patient’s prognosis, synchronous chemoradiotherapy has always been the standard treatment for limited-stage small-cell lung cancer (LS-SCLC). Objectives: Immuno-combined and radio-combined therapy in LS-SCLC has been applied in clinical practice, but what is the best for LS-SCLC? Design: This was a retrospective cohort study. Methods: Patients with LS-SCLC from January 2019 to December 2023 were retrospectively screened and divided into three groups according to the initial treatment regimen whether included immune-combined and radio-combined treatment. Univariate and multivariate Cox regression were used to analyze the predictors affecting the survival of LS-SCLC, and the progression pattern of patients and the occurrence of adverse events (AEs) were also recorded. Results: In this study, the median overall survival (OS) was 15.8 months, not yet reached (NR) and NR, and the median progression-free survival (PFS) was 11.7, 20.9, and 18.9 months in the immunotherapy combined chemotherapy ( N  = 34), immune combined chemoradiotherapy ( N  = 26), and chemoradiotherapy ( N  = 53) groups, respectively. OS and PFS were significantly prolonged in the radio-combined groups compared with the non-radio-combined group, and there was no significant difference between the radio-combined groups, namely immunotherapy combined chemoradiotherapy and chemoradiotherapy groups. In this study, we also constructed some indexes to predict prognosis for LS-SCLC, derived neutrophil and lymphocyte ratios were significantly associated with worse survival, and systemic inflammatory index and neuron-specific enolase (NSE) levels were significantly associated with shorter PFS. The primary organs of progression remained the lung and brain, the main immune-related AE was hypothyroidism, and the radiation-related AE was pneumonia. Conclusion: Radiation-combined therapy still plays an important role in LS-SCLC in the era of immunotherapy, and clinicians cannot abandon the use of radiation therapy in the initial treatment plan for LS-SCLC.